2021
DOI: 10.1111/ijd.15655
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy accuracy for lateral margin assessment of distinct basal cell carcinoma subtypes treated by Mohs micrographic surgery in 368 cases

Abstract: can be seen. In more than half of the patients, nevus of Ota may be associated with ocular melanocytosis, which can involve conjunctiva, sclera, uveal tract, retina, and optic nerve. Although it is usually benign, there is a low risk of developing melanoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Among these, 4 were excluded (case reports and noncomparative studies) [16][17][18][19]. Three research letters were excluded [11,20,21]. Among these research The mean number of Mohs stages in each study group was specified in 5 articles [4,[6][7][8][9].…”
Section: Results Of the Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 4 were excluded (case reports and noncomparative studies) [16][17][18][19]. Three research letters were excluded [11,20,21]. Among these research The mean number of Mohs stages in each study group was specified in 5 articles [4,[6][7][8][9].…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Two studies reported the number of recurrences after MMS [4][5][6][7][8][9]. One of these letters, two compared dermoscopy to naked eye examination in BCC margin evaluation but the number of Mohs stages in each study group expressed in mean with standard deviation was not available [11,20]; and one article included only BCC evaluated using dermoscopy prior to MMS [21].…”
Section: Effects Of Interventionsmentioning
confidence: 99%
“…In contrast, telangiectatic vessels from chronic sun damage are smaller, less focused and dull-red. However, when BCC develops on severely sun-damaged skin with numerous telangiectasias, it might be challenging to discriminate them from tumoral vessels and delineate the tumor [ 3 ].…”
Section: Introductionmentioning
confidence: 99%